2017
DOI: 10.1088/1361-6501/aa87e1
|View full text |Cite
|
Sign up to set email alerts
|

High-spatial-resolution electron density measurement by Langmuir probe for multi-point observations using tiny spacecraft

Abstract: A method for evaluating electron density using a single fixed-bias Langmuir probe is presented. The technique allows for high-spatio-temporal resolution electron density measurements, which can be effectively carried out by tiny spacecraft for multi-point observations in the ionosphere. The results are compared with the multi-needle Langmuir probe system, which is a scientific instrument developed at the University of Oslo comprising four fixed-bias cylindrical probes that allow small-scale plasma density stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…1, where three operational regions of electron saturation, electron retardation, and ion saturation are separated by the plasma potential (V p ) and the floating potential (V f ). (19) Note that the magnitude of the ion current is exaggerated for illustration purposes.…”
Section: Langmuir Probe Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, where three operational regions of electron saturation, electron retardation, and ion saturation are separated by the plasma potential (V p ) and the floating potential (V f ). (19) Note that the magnitude of the ion current is exaggerated for illustration purposes.…”
Section: Langmuir Probe Diagnostic Methodsmentioning
confidence: 99%
“…To achieve high-spatialresolution measurement to detect the fine structure of the plasma, the sampling frequency must be increased. (19) Using an A/D conversion module with a built-in MCU can simplify the design to achieve a sampling frequency ( f samp ) of 10 kSPS. From f samp and the satellite speed (V sat ), the spatial resolution (R spa ) can be obtained from Eq.…”
Section: Overall System Designmentioning
confidence: 99%
“…More details of the electron emitter development can be found in . Test results of the electron emitter have been obtained, showing that with a limited power consumption of 100 mW, emitted beam currents could reach up to 54 µA for the accelerating voltage of 38 V on the QB50 satellites (Hoang et al, 2017). Electrons emerge from the electron emitter with a kinetic energy of 38 eV, which corresponds to about 3600 km/s with respect to the satellite.…”
Section: Miniaturized Thermionic Electron Emitter (Mtee)mentioning
confidence: 99%
“…However, the probes are cleaned by solar heating and ion sputtering over its mission in orbit. Furthermore, the work in Hoang et al (2017) showed that the m-NLP probes are barely affected by contamination due to water vapor impurities in space. To ensure a good measurement performance against likely impacts of contamination, in-flight probe performance validation by sweeping probe biases is regularly executed.…”
Section: Probe and Boom System Designmentioning
confidence: 99%
“…More details of the electron emitter development can be found in Bekkeng et al (2017). Test results of the electron emitter have been obtained, showing that with a limited power consumption of 100 mW, emitted beam currents could reach up to 54 µA for the accelerating voltage of 38 V on the QB50 satellites (Hoang et al 2017). Electrons emerge from the electron emitter with a kinetic energy of 38 eV, which corresponds to about 3600 km/s with respect to the satellite.…”
Section: Miniaturized Thermionic Electron Emitter (Mtee)mentioning
confidence: 99%